Studi Literatur Tentang Perseteruan Antara Yahudi Dengan Samaria Berdasarkan Informasi Yohanes 4:9 - pika idaman jernih hia; Meniati Hia (Jurnal Missio Cristo, 2023)
The two groups between Jews and Samaritans are not widely known by Christians in general. The relationship between these two camps has attracted the attention of many people, regarding Jesus' ministry to the Samaritan woman who said: "(Because the Jews did not associate with the Samaritans)" John 4:9. The author of John does not provide complete information regarding the conflict of these two groups, even though they are both God's chosen people. Then, another problem is that several times God made the Samaritans as an example for the Jews to emulate, but the promise of the coming of the Messiah always puts the Jews first. Therefore, the authors conducted qualitative research using literature/library studies. To find out the main reasons for the animosity of both sides so that these two groups of God's people do not get along with each other. Then does the horizontal conflict on both sides affect their status before Allah. Because the author concludes that between the two sides there is no tribe that is prioritized by the Lord Jesus. Abstrak Bahasa Indonesia Kedua kelompok antara Yahudi dengan Samaria tidak terlalu banyak diketahui oleh umat Kristen pada umumnya. Hubungan dari kedua kubu ini, telah menarik perhatian banyak orang, terkait pelayanan Yesus kepada perempuan Samaria yang mengatakan: “(Sebab orang Yahudi tidak bergaul dengan orang Samaria)”  Yohanes 4:9. Penulis Yohanes tidak memberikan keterangan yang lengkap terkait konflik dari kedua kelompok ini, padahal mereka adalah sama-sama kaum pilihan Allah. Kemudian, persoalan yang lain adalah beberapa kali Tuhan menjadikan orang Samaria sebagai contoh bagi orang Yahudi untuk diteladani, tetapi janji kedatangan Mesias selalu mengutamakan orang Yahudi.   Oleh sebab itu, penulis melakukan penelitian kualitatif dengan menggunakan studi literatur/ pustaka. Untuk mengetahui  alasan utama permusuhan dari kedua belah pihak sehingga kedua kelompok umat Allah ini tidak saling bergaul. Kemudian apakah konflik horinzontal dikedua belah pihak mempengaruhi status mereka dihadapan Allah. Sebab penulis berkesimpulan bahwa diantara kedua belah pihak tidak ada suku yang lebih di utamakan oleh Tuhan Yesus.